Spectrometric Estimation of Rabeprazole Sodium from Tablet Formulation - Pillai, S.; Singhvi, I. (Asian Journal of Chemistry, 2010)
Two simple and sensitive visible spectrophotometric methods have been developed for the quantitative estimation of rabeprazole sodium from its tablet formulation. The first developed method is based on formation of chloroform extractable coloured complex of drug with bromo phenol red and the second developed method is the formation of yellowish brown complex of drug with crystal violet. The chloroform extracted complex of the drug with bromo phenol red showed absorbance maxima at 418 nm and linearity was observed in the concentration range of 10–50 μg/mL. The complex of the drug with crystal violet showed absorbance maxima at 412 nm and linearity was observed in the concentration range of 100–600 μg/mL. Results of analysis for both the developed methods were validated statistically and by recovery studies.